Analisis Perbandingan Penerapan PP no 46 tahun 2013 dengan UU no 36 tahun 2008 pada PT Trio Infotek Batam - Dianaswara Sindari; Arniati Arniati (Politeknik Negeri Batam, 2015)
In mid-2013 The government had issued the new regulation of Taxation in PP No 46 Year 2013. PP 46 introduces a final tax regime on business income of certain individual and corporate taxpayers, excluding permanent establishments, with a gross turnover of less than Rp 4.8 billion (USD 482,000) per annum. This PP 46 is not a replacement for the prior regulation of UU No. 36 Year 2008, this regulation special for SMEs. There were some differences to In the UU 36 Year 2008 to be found between the two regulations. They were different in terms of the calculation, payment, or even the reporting. The comparation of these two regulations would give a conclusion as to a service-provided company, the PP 46 is benefiting them in term of paying less tax after the calculation every year.